Global Trends and Challenges in Teacher Training: A Bibliometric Analysis (2019–2024) - Mohieddin Masoud; Abdulnasir Alsayd; Majdy kasheem (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
By giving teachers the necessary tools, teacher training plays a critical role in raising the standard of education. Training programs that are accessible and structured are becoming more and more important as educational demands change. The usefulness of teacher training frameworks, the incorporation of contemporary educational approaches, and the difficulties in obtaining and executing these programs are all examined in this study. This study examines global trends in teacher training literature (2019–2024) using Scopus and bibliometric analysis. Thematic focuses, important contributors, and publication trends were evaluated by data analysis using R/R-Studio, VoSviewer, and Microsoft Excel. Despite a rise in research activity, the results indicate a decreasing annual growth rate of publications. With a focus on particular locations, the study identifies important journals, authors, organizations, and nations influencing research on teacher preparation. Results show that training that is well-organized and updated often improves student performance and instructional efficacy. Adaptability to different classrooms is enhanced by the integration of inclusive education and technology. Nonetheless, there are still gaps in our knowledge of the long-term effects of training and in guaranteeing fair access to professional growth. When creating evidence-based teacher training programs, policymakers, educational institutions, and training providers use these insights as a guide. Comparative evaluations of training approaches, long-term efficacy, and international cooperation tactics in teacher education should all be investigated in future studies. For education systems around the world to advance, teacher training programs must be strengthened.